99mTechnetium‐pyrophosphate scintigraphy: a practical guide for early diagnosis of transthyretin amyloid cardiomyopathy. (29th November 2021) - Tahara, Nobuhiro; Lairez, Olivier; Endo, Jin; Okada, Atsushi; Ueda, Mitsuharu; Ishii, Tomonori; Kitano, Yoshinobu; Lee, Hahn‐Ey; Russo, Eleonora; Kubo, Toru
Abstract: Transthyretin amyloid cardiomyopathy (ATTR‐CM) is caused by the cardiac deposition of insoluble amyloid fibrils formed by misfolded transthyretin proteins and is associated with various cardiac symptoms, such as progressive heart failure, conduction disturbance, and arrhythmia. The implementation of 99m technetium ( 99m Tc)‐labelled bone radiotracer scintigraphy for diagnosing ATTR‐CM has enabled accurate diagnosis of the disease with high sensitivity and specificity and positioned this diagnostic modality as an integral part of disease diagnostic algorithms. In 2020, 99m Tc‐pyrophosphate scintigraphy received exceptional approval for Japanese national health insurance reimbursement as a diagnostic method of ATTR‐CM. Nevertheless, the utility of 99m Tc‐labelled bone radiotracer scintigraphy and the importance of an early diagnosis of suspected ATTR‐CM using this technique have yet to be internalized as common practice by general cardiologists, and guidance on daily clinical scenarios to consider this technique for a diagnosis of suspected ATTR‐CM is warranted. In this review, we discuss the utility of 99m Tc‐labelled bone radiotracer scintigraphy for the early diagnosis of ATTR‐CM based on published literature and the outcomes of an advisory board meeting. This review also discusses clinical scenarios that could support early diagnosis of suspected ATTR‐CM as well as common pitfalls, correct implementation, and future perspectives of 99m Tc‐labelled bone radiotracer scintigraphy in daily clinical practice. The clinical scenarios to consider 99m Tc‐labelled bone radiotracer scintigraphy in daily practice may include, but are not limited to, patients with a family history of the hereditary type of disease; elderly patients (aged ≥60 years) with unexplained cardiac findings (e.g. cardiac hypertrophy associated with abnormalities on an electrocardiogram, heart failure with preserved ejection fraction associated with unexplained left ventricular hypertrophy, and heart failure with reduced ejection fraction associated with atrial fibrillation and left ventricular hypertrophy); and patients with cardiac hypertrophy associated with diastolic dysfunction, right ventricular/interatrial septum/valve thickness, left ventricular sparkling, or apical sparing. Cardiac hypertrophy and persistent elevation in cardiac troponin in elderly patients are also suggestive of ATTR‐CM. 99m Tc‐labelled bone radiotracer scintigraphy is also recommended in patients with characteristic cardiac magnetic resonance findings (e.g. diffuse subendocardial late gadolinium enhancement patterns, native T1 increase, and increase in extracellular volume) or patients with cardiac hypertrophy and bilateral carpal tunnel syndrome.